Unveiling the potential of Daldinia eschscholtzii MFLUCC 19-0629 through bioactivity and bioinformatics studies for enhanced sustainable agriculture production - Brooks, Siraprapa; Weaver, Jack A.; Klomchit, Anthikan; Alharthi, Shumukh A.; Onlamun, Thanyarat; Nurani, Rithika; Vong, Thienthu Khanh; Alberti, Fabrizio; Greco, Claudio (Frontiers in Chemical Biology, 2024)
Endophytic fungi constitute a rich source of secondary metabolites that can be manipulated to produce desirable novel analogs for combating current agricultural challenges for crop production, especially controlling plant disease. The endophytic fungus Daldinia eschscholtzii MFLUCC 19-0629, was newly isolated from tropical ancient plants, Oncosperma sp., and displays a broad-spectrum of antifungal and antibacterial activities against several plant pathogens including Ralstonia solanacearum, Fusarium oxysporum, Colletotrichum gloeosporioides, Colletotrichum acutatum, Stagonosporopsis cucurbitacearum, Corynespora cassiicola and Stemphylium spp. A high-quality genome sequence was obtained using Oxford nanopore technology, the accuracy and length of reads resulting in no need for Illumina or other sequencing techniques, for D. eschscholtzii MFLUCC 19-0629, resulting in a genome size of 37.56 Mb assembled over 11 contigs of significant size, likely to be at the chromosomal level. Bioinformatics analysis revealed that this strain is biosynthetically talented encoding 67 predicted biosynthetic gene clusters (BGCs). Only eight of the 67 BGCs matched or demonstrated high similarity to previously characterized BGCs linked to the production of known secondary metabolites. The high number of predicted unknown BGCs makes this strain a promising source of novel natural products. The discovery that D. eschscholtzii MFLUCC 19-0629 has a broad spectrum of antimicrobial activity against seven major plant pathogenic microorganisms relevant to crop production and its complete genome sequence carries immense importance in the advancement of novel microbial biocontrol agents (MBCAs). This also unveils the prospect of uncovering new compounds that could be utilized for sustainable agriculture and pharmaceutical purposes.